ALCOHOL, DRUG USE, AND INJURIES IN TRAFFIC CRASHES AND ABUSES TREATED IN EMERGENCY ROOMS - Malaga, Hernán (2020)
Following the regional protocol designed by the PAHO alcohol and drug program, the relative frequency of injuries in traffi c crashes and injuries, which reached an emergency center with alcohol and / or drugs, Th e Casimiro Ulloa National Hospital (HEJCU) was chosen for the period October 2018 to July 2019. Th e study population was that of the patients who gave us informed consent and the team in charge of sampling, fi lled out the ad-hoc form and collected the results of the breathalyzer and drug test. Th e high frequency of patients who did not give their consent would reveal the high degree of sensitivity towards the detection of alcoholics and drug addicts existing in the city, 15% of alcoholics were detected, 5% of marijuana users, 3% of cocaine and one opiate. An association was detected between alcohol and drug use. Th e drug detection program should incorporate a drug detection system, which should be extended to pedestrians.